The adventures of Tintin : The crab with golden claws - Hergé (Little, Brown, 2008)
In volume 3, the reader will participate in new adventures full of adventure and surprises. Tintin and his dog Snowy, along with Captain Haddock and Professor Calculus, will face new challenges, from exploring mysterious forests to solving thrilling cases and confronting dangerous enemies.